PENGAWASAN UNIT APRON MOVEMENT CONTROL (AMC) DAN DISIPLIN PENGGUNA JASA DI APRON BANDAR UDARA INTERNASIONAL HUSEIN SASTRANEGARA - Muhammad Arif Hernawan; Faisal Akbar; Alit Sodikin (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
The international trade and activities have elevated the bustles in Husein Sastranegara  International Airport, Bandung. Therefore, it needs more control in apron administered by the Apron Movement Control (AMC) that has licenses and ratings to do the job as the supervisor of flight operation activities, control, aircraft movements, traffic, and cleanliness control in the apron areas.  The objectiveof this study is to analyze the relationships between control unit in Apron Movement Control (AMC) and the discipline of apron service users in Husein Sastranegara International Airport. The research method used in this study is qualitative design. The result of the study based on the hypothesis shows that the value of t count = 6.71 while  t table = 1.734 in level of significance is 5% .  Since t count > t table (6.71>1.734) consequently, Ha is accepted and Ho is denied.   This study shows that the hypothesis is proved to be true that there is a relationship between the control unit of Apron Movement Control (AMC) and the discipline of apron service users in Husein Sastranegara    International Airport, Bandung in 2014.